Estudio microbiológico de un microencapsulado a base de Ilex Guayusa, Vernonanthura patens y Theobroma cacao (cascarilla de cacao) - Gavin-Quinchuela, Karina Estefanie (2018)
Introduction: Microencapsulation provide a tool to protect natural resources extracts and compounds from the action of biotic, abiotic and biological factors. In this sense, it emerges as a reliable methodology not only for the food industry, but also for the fields of nutrition and health, where the stability, efficacy and bioavailability of these extracts and compounds are necessary. Objectives: To analyze a microencapsulse based on Ilex Guayusa, Vernonanthura patens and cocoa husk by means of bromatological and microbiological tests for the characterization of this product. Methods: Microbiological and bromatological studies were carried out according to the INEN 2381 standard, the samples were dried and sieved for further elaboration of the beverage. For the microbiological analyzes, the DNA was extracted by a kit and subsequently analyzed by Sanger sequencing. The bromatological analyzes performed were humidity, total ash, proteins, fats and fiber under the protocols of the CIBE Bioproductos laboratory. Results: In the microencapsulation a 95.75% carbohydrate was obtained, this percentage being the highest in comparison with the rest of the macronutrients. Fat obtained 1.20% and protein was 0.5%. Moisture parameters resulted in 1.75%. The microbiological analyzes reported that the product is safe due to the absence of pathogenic bacteria such as Shigella and salmonella spp and the low load of other microorganisms. Conclusions: The project allowed the determination of bromatological and microbiological analyzes. From these first analyzes it was identified that the carbohydrate content predominates in the product (˃95%), due to the maltodextrin addiction to the beverage as an encapsulating agent. The microencapsulated product is considered safe because they meet the established standards.